Savva, Athina - (:unkn) unknown (My University, 2026)
Athina Savva is an Intern at ERATOSTHENES Centre of Excellence of the Cyprus University of Technology in the Environment and Climate department of the Study of the Atmosphere and Atmospheric Remote Sensing team. She graduated from the Aristotle University of Thessaloniki with a BSc in Physics focused on the Study of the Atmosphere. Currently she is a MSc student in the department of Environment of the University of the Aegean in Global Environmental Change, Management and Technology. At ERATOSTHENES CoE she works in Aerosol classification with LIDAR and AERONET data and she reviews the daily status and profiles of the atmosphere. Her interests are in the Study of the Atmosphere, Air pollution, Aerosol classification, Energy, Renewable Energy and Climate Change.